Antimicrobial Consumption in the Livestock Sector in Bhutan: Volumes, Values, Rates, and Trends for the Period 2017-2021 - Ratna B. Gurung; Karma P. Zangmo; James R. Gilkerson; Glenn F. Browning; Angeline S. Ferdinand; Mauricio J. C. Coppo (MDPI AG, 2023)
Data on the use of antimicrobials in humans and livestock may provide evidence to guide policy changes to mitigate the risk of antimicrobial resistance (AMR). However, there is limited information available about antimicrobial use in livestock in low- and middle-income countries, even though these nations are most vulnerable to the impact of AMR. This study aimed to assess the consumption of veterinary antimicrobials in Bhutan and identify areas for improvement to reduce the use of antimicrobials in livestock. National data on livestock numbers and annual procurement of veterinary antimicrobials over five years (2017-2021) were used to calculate rates of antimicrobial consumption and annual national expenditure on veterinary antimicrobials in Bhutan. The rate of antimicrobial consumption in Bhutan was 3.83 mg per population correction unit, which is lower than most countries in Europe, comparable with the rates of consumption in Iceland and Norway, and approximately 120-fold lower than published rates of antimicrobial consumption in South Asian countries, including Nepal and Pakistan. The low rates of antimicrobial consumption by the animal health sector in Bhutan could be attributable to stronger governance of antimicrobial use in Bhutan, higher levels of compliance with regulation, and better adherence to standard guidelines for antimicrobial treatment of livestock.